Removal of acid blue 25 dye by using dried water hyacinth from aqueos solution - Nurfani Ekawati, Musthafa (2010)
Water hyacinth(Eichhornia crassipes)is a free floating aquatic weeds that robustness in its growth used as an adsorbent to remove Acid Blue 25 dye from aqueous solution. The parameters studied include the adsorbent dosage,initial dye concentration,pH,and also contact time in a batch adsorption process at room temperature 21ºC.The results shows the optimum conditions for each parameter studied, adsorbent dosage at 0.60 g,initial concentration 400 mg/L, pH 2 and 100 minutes contact time.The samples after the dye uptake were analyzed by using UV-Vis spectrophotometer. Furthermore,before and after the experiments,FTIR analyses were studied to know the functional groups of the water hyacinth.In addition,the equilibrium data fitted well pseudo-second order kinetics,Langmuir and Freundlich isotherm.The maximum sorption capacities for Langmuir equation were 83.33 mg/g whereas the amount of n for Freundlich is favourable.While for pseudo-second-order kinetics,it has a low error for equilibrium sorption capacity for experimental and calculated values.This study is favourable and economically feasible for the removal of Acid Blue 25.